2011
DOI: 10.1371/journal.pone.0016713
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of TRPV4 Activity following Selective Activation by Small Molecule Agonist GSK1016790A

Abstract: TRPV4 (Transient Receptor Potential Vanilloid 4) channels are activated by a wide range of stimuli, including hypotonic stress, non-noxious heat and mechanical stress and some small molecule agonists (e.g. phorbol ester 4α-PDD). GSK1016790A (GSK101) is a recently discovered specific small molecule agonist of TRPV4. Its effects on physical determinants of TRPV4 activity were evaluated in HeLa cells transiently transfected with TRPV4 (HeLa-TRPV4). GSK101 (10 nM) causes a TRPV4 specific Ca2+ influx in HeLa-TRPV4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
91
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 45 publications
16
91
1
Order By: Relevance
“…The GSK101-induced time course of [Ca 2ϩ ] i was relatively slow, typically reaching a peak value within 1-6 min. The results are consistent with our earlier characterization of GSK101 in TRPV4-transfected HeLa cells and in the M-1 collecting duct cells which endogenously express TRPV4 (19,25). Comparison of the responses of individual cells from a single split-opened CCD demonstrates variable responses from cell to cell that are likely reflective of the individual properties and TRPV4 expression levels of different cells from a single tubule (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The GSK101-induced time course of [Ca 2ϩ ] i was relatively slow, typically reaching a peak value within 1-6 min. The results are consistent with our earlier characterization of GSK101 in TRPV4-transfected HeLa cells and in the M-1 collecting duct cells which endogenously express TRPV4 (19,25). Comparison of the responses of individual cells from a single split-opened CCD demonstrates variable responses from cell to cell that are likely reflective of the individual properties and TRPV4 expression levels of different cells from a single tubule (Fig.…”
Section: Resultssupporting
confidence: 93%
“…To verify the TRPV4 specificity of our antibody for TRPV4, in separate studies we have demonstrated that our antibody (directed at the C terminus, Alomone Laboratory anti-TRPV4) recognized an appropriate double band (ϳ100 kDa) for TRPV4 in TRPV4-transfected HEK cells, but not in nontransfected HEK cells (19). Immunocytochemistry and functional assays confirmed identification of TRPV4 only in the TRPV4-expressing cells.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The Fura-2 fluorescence intensity ratio was determined by excitation (an average for ϳ300 ms) at 340 nm and 380 nm and calculating the ratio of the emission intensities at 511 nm in the usual manner every 5 s. We observed no significant Fura-2 bleaching and minimal Fura-2 leakage at both wavelengths during the experiments. The changes in the ratio were converted to intracellular Ca 2ϩ concentrations using the calibration methods as we have done before (34,35). Experimental traces from individual cells were inspected visually prior to acceptance.…”
Section: Methodsmentioning
confidence: 99%